Evaluation of left atrial linear ablation using contiguous and optimized radiofrequency lesions: the ALINE study. Issue Volume 20:Issue FI 3(2018) (8th January 2018) - Wolf, Michael; El Haddad, Milad; Fedida, Joël; Taghji, Philippe; Van Beeumen, Katarina; Strisciuglio, Teresa; De Pooter, Jan; Lepièce, Caroline; Vandekerckhove, Yves; Tavernier, René; Duytschaever, Mattias; Knecht, Sébastien
Abstract: Aims: Achieving block across linear lesions is challenging. We prospectively evaluated radiofrequency (RF) linear ablation at the roof and mitral isthmus (MI) using point-by-point contiguous and optimized RF lesions. Methods and results: Forty-one consecutive patients with symptomatic persistent AF underwent stepwise contact force (CF)-guided catheter ablation during ongoing AF. A single linear set of RF lesions was delivered at the roof and posterior MI according to the 'Atrial LINEar' (ALINE) criteria, i.e. point-by-point RF delivery (up to 35 W) respecting strict criteria of contiguity (inter-lesion distance ≤ 6 mm) and indirect lesion depth assessment (ablation index ≥550). We assessed the incidence of bidirectional block across both lines only after restoration of sinus rhythm. After a median RF time of 7 min [interquartile range (IQR) 5–9], first-pass block across roof lines was observed in 38 of 41 (93%) patients. Final bidirectional roof block was achieved in 40 of 41 (98%) patients. First-pass block was observed in 8 of 35 (23%) MI lines, after a median RF time of 8 min (IQR 7–12). Additional endo- and epicardial (54% of patients) RF applications resulted in final bidirectional MI block in 28 of 35 (80%) patients. During a median follow-up of 396 (IQR 310–442) days, 12 patients underwent repeat procedures, with conduction recovery in 4 of 12 and 5 of 10 previously blocked roof lines and MI lines, respectively. No complications occurred. Conclusion: Anatomical linear ablation using contiguous and optimized RF lesions results in a high rate of first-pass block at the roof but not at the MI. Due to its complex 3D architecture, the MI frequently requires additional endo- and epicardial RF lesions to be blocked.